COMMUNICATIVE COMPETENCE IN STUDENTS 'FOREIGN LANGUAGE LEARNING AS THE MAIN CONTENT OF THE EDUCATIONAL PROCESS (Conference Zone, 2022)
This article focuses on the development of foreign language competence in students and their inclusion in communicative and professional roles, with the aim of teaching them to be socially, professionally and communicatively successful.